PEMBERDAYAAN REMAJA MELALUI PEMBINAAN KARAKTER SEBAGAI UPAYA PENCEGAHAN KENAKALAN REMAJA - Nur Meladia; Muhammad Sahlan; Rindi Setyo Rahayu; M. Syaikah Firjatullah (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
Juvenile delinquency is one of the issues that requires attention because it can affect the character development and social life of students. One form of behavior that needs to be prevented in educational environments is bullying, which can have an impact on students’ social relationships and psychological well-being. This activity aimed to improve adolescents’ understanding and awareness of the importance of character development as an effort to prevent juvenile delinquency, particularly bullying behavior. The activity was conducted on July 25, 2026, at MTs Tahfidzul Qur’an in Sembulung Village, Cluring District, Banyuwangi Regency, involving 14 participants. The implementation method used a Participatory Action Research (PAR) approach, which positioned participants as active contributors in identifying problems, implementing activities, and conducting reflection. The activities included material delivery by a Guidance and Counseling (BK) teacher and university students, interactive discussions, and an anti-bullying declaration. At the final stage, participants wrote their anti-bullying commitments on provided paper and attached them to a sheet of buffalo paper as a form of collective commitment to creating a safe and respectful school environment. The results showed that participants actively participated in the activities and gained an understanding of the forms, impacts, and prevention of bullying through character development. The declaration activity also provided a form of direct participation for students in building a commitment to positive behavior. Therefore, character development through a participatory approach can serve as a preventive effort to increase adolescents’ awareness and encourage the creation of an educational environment free from bullying.